2017
DOI: 10.1002/ecy.1939
|View full text |Cite
|
Sign up to set email alerts
|

An arthropod survival strategy in a frequently burned forest

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Many non-flying invertebrates (e.g. ants, stick insects, wingless nymphs of grasshoppers, spiders) appear to be able to detect fires well in advance of the front, presumably from smoke or sound; they attempt to shelter from fires by either moving into the soil, or by climbing to the tops of trees (Sensenig et al 2017;Dell et al 2017). Some animals in fire-prone ecosystems do not appear to show stressed behaviour in the presence of fire, but move calmly and search for a safe site or for a low flammability patch (Whelan 1995).…”
Section: Fauna Adapted To Fire-prone Habitatsmentioning
confidence: 99%
“…Many non-flying invertebrates (e.g. ants, stick insects, wingless nymphs of grasshoppers, spiders) appear to be able to detect fires well in advance of the front, presumably from smoke or sound; they attempt to shelter from fires by either moving into the soil, or by climbing to the tops of trees (Sensenig et al 2017;Dell et al 2017). Some animals in fire-prone ecosystems do not appear to show stressed behaviour in the presence of fire, but move calmly and search for a safe site or for a low flammability patch (Whelan 1995).…”
Section: Fauna Adapted To Fire-prone Habitatsmentioning
confidence: 99%
“…However, late-season fires at Kapalga caused 30% mortality in frill-necked lizards (Griffiths & Christian, 1996), and my unpublished observations of insects climbing up trees in response to smoke from experimental fires at the Territory Wildlife Park (cf. Dell et al, 2017) indicate an evolutionary response to direct fire-induced mortality.…”
Section: Insight 2 the Main Effects Of Fire On Fauna Are Indirect mentioning
confidence: 99%
“…Foraging success in black‐backed woodpeckers Picoides arcticus , for example, increases following severe fire due to increased availability of preferred arthropod prey (Rota et al ., 2015). Similarly, arthropods available to bark‐foraging birds in southern pine forests frequently move from the understory onto pine boles (Hanula & Franzreb, 1998), and low‐intensity prescribed fire may stimulate this type of vertical movement of RCW arthropod prey (Dell et al ., 2017) thereby increasing foraging success. Our finding that area treated with prescribed fire within the past 2 years had direct positive effects on RCWs aligns with several studies on cavity‐nesting and bark‐foraging birds that found fire effects on bird productivity were related to direct effects of chemical cues that attracted preferred arthropod prey to burned areas, independent of direct effects of fire on forest structure (Lyons et al ., 2008; Nappi & Drapeau, 2009; Russell et al ., 2009).…”
Section: Discussionmentioning
confidence: 99%